Prostitution and risk of HIV: female prostitutes in London. Issue 6900 (7th August 1993) - Ward, H; Day, S; Mezzone, J; Dunlop, L; Donegan, C; Farrar, S; Whitaker, L; Harris, J R; Miller, D L
Abstract : OBJECTIVE--To measure the prevalence of HIV and to describe established risk factors in female prostitutes. DESIGN--A cross sectional survey. SETTING--A genitourinary medicine clinic, streets, and magistrates' courts in London. SUBJECTS--280 female prostitutes recruited between April 1989 and August 1991. MAIN OUTCOME MEASURES--Infection with HIV-1, reported risk behaviours, and prevalence of sexually transmitted infections. RESULTS--228 of the women had HIV tests, and two (0.9% (95% confidence interval 0% to 2.1%)) were infected with HIV-1. Reported use of condoms was high for commercial clients and low for non-paying partners: 98% (251/255) of women used condoms with all clients and 12% (25/207) with non-paying partners for vaginal intercourse. Twenty two women were current or past injecting drug users. Of the 193 women examined for sexually transmitted infections, 27 had an acute infection (gonorrhoea, chlamydia, trichomonas, or primary genital herpes) at the time of interview. Infection was associated with younger age and increasing numbers of non-paying sexual partners, but not with duration of prostitution, numbers of clients, or reports of condom failures. When age and numbers of non-paying partners were analysed by logistic regression they remained significantly associated with sexually transmitted infections. CONCLUSIONS--A large and diverse sample of prostitutes had a low prevalence of infection with HIV and high levels of use of condoms in commercial sex. There was a significant risk of other sexually transmitted infections associated with prostitutes' non-commercial sexual relationships, in which unprotected sex is common. Interventions to reduce the risk of sexually transmitted infections in prostitutes should address both commercial and non-commercial sexual partnerships.